Analysis of somatic mutation enrichment in gene expression landscapes for cancer cell lines - Arakelyan, A. A. (ՀՀ ԳԱԱ հրատ.)
This study is aimed at assessing the association between somatic mutations and gene expression in NCI-60 cancer cell lines using publicly available dataset and bioinformatics approaches. The study results demonstrate that the deregulation in gene expression profiles in cancer only partly can be attributed to the presence of somatic mutations, which implies the importance of assessment of epigenetic mechanisms of regulation and multi-omics data integration for cancer systems biology.Ուսումնասիրվել է NCI-60 քաղցկեղային բջջային գծերում լայնածավալ գեների էքսպրեսիայի և սոմատիկ մուտացիաների կապը: Հետազոտության արդյունքները ցույց են տվել, որ դիֆերենցիալ գեների էքսպրեսիան միայն մասամբ են ասոցիացված մուտացիաների առկայությամբ, ինչը առաջ է բերում էպիգենետիկական մեխանիզմների ուսումնասիրության անհրաժեշտությունը և մուլտիոմիկայի տվյալների ինտեգրումը քաղցկեղների համակարգային կենսաբանության ոլորտում:Проведена оценка влияния соматических мутаций на экспрессию генов в раковых клеточных линиях NCI-60. Результаты исследования показали, что дифференциальная экспрессия генов только частично зависит от наличия мутаций, что в свою очередь указывает на необходимость исследования эпигенетических механизмов регуляции экспрессии и интеграции мультиомных данных в контексте системной биологии опухолей.
Keywords: Biology; Molecular Biology